2002
DOI: 10.1074/jbc.m201768200
|View full text |Cite
|
Sign up to set email alerts
|

The Troponin Tail Domain Promotes a Conformational State of the Thin Filament That Suppresses Myosin Activity

Abstract: Calcium binding to the thin filament protein troponin is required for cardiac and skeletal muscles to contract, and several studies indicate that this regulation involves shifting the tropomyosin position on the actin filament. When the regulatory sites of troponin do not have bound Ca 2ϩ , tropomyosin is located on the actin outer domain. In this position tropomyosin sterically interferes with much more of the myosin-binding site than it does in the presence of Ca 2ϩ , and therefore contraction is inhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 85 publications
12
96
0
Order By: Relevance
“…Our results can be compared with those reported for a similar TnT 1 fragment from bovine cardiac troponin by Tobacman et al (44). Their TnT 1 fragment inhibits S1 ATPase, in vitro motility, and S1-ADP binding assays, in agreement with our data.…”
Section: ϫ1 Msupporting
confidence: 82%
“…Our results can be compared with those reported for a similar TnT 1 fragment from bovine cardiac troponin by Tobacman et al (44). Their TnT 1 fragment inhibits S1 ATPase, in vitro motility, and S1-ADP binding assays, in agreement with our data.…”
Section: ϫ1 Msupporting
confidence: 82%
“…Recent work has suggested that TnT may in fact have a significant role in modulating regulation, which may contribute to the differences between the two cardiac and skeletal complexes seen here (9,10). Although our study characterized skeletal TnT effects using similar assays to those presented here, the other used motility and ATPase measurements.…”
Section: Table Imentioning
confidence: 80%
“…TnT also influences the Tm-Tm communication along the filament via its interaction at the Tm-Tm overlap (8) and has been shown recently to also influence regulation directly. Our own work has shown the TnT 1 fragment of skeletal TnT effects the open-closed equilibrium significantly reducing K T (9), whereas work on a similar cardiac TnT 1 fragment has shown strong inhibition of the actinactivated myosin ATPase (10).…”
mentioning
confidence: 99%
“…2 plays many important roles in striated muscle contraction, providing structural stability to the troponin complex and actively participating in the Ca 2ϩ -dependent regulation of contraction (1)(2)(3)(4)(5). TnT was first associated with heart disease in 1994 where three mutations were reported to cause Familial Hypertrophic Cardiomyopathy (FHC) (6).…”
Section: Troponin T (Tnt)mentioning
confidence: 99%